Reviewers - en Psicología, Actualidades (2022)
Javier Prado, Servicio Aragonés de Salud, España Dora Herrera, Pontificia Universidad Católica del Perú, Perú Norman Moreno, Universidad de San Buenaventura, Colombia Ana María Jurado, Universidad de Costa Rica, Costa Rica Pedro Crocce Carlotto, Universidade Federal de Santa Catarina, Brasil Fernanda Robert Ferrel, Universidad de Madgalena, Colombia Vicente Morell Mengual, Universidad de Valencia, España Luis Diego Conejo, Universidad Nacional, Costa Rica Pedro Cortez, Universidade Metodista de São Paulo, Brasil Ana Paula Couto, Universidade Federal di Rio Grande do Sul, Brasil Evelin Fernández Castillo, Universidad Central “Marta Abreu” de Las Villas, Cuba Yunier Broche, Universidad Central “Marta Abreu” de Las Villas, Cuba Catalina Argüello, Universidad Internacional de la Rioja, España Larissa Timofeeva, Universidad de Alicante, España Vanessa Pérez Martínez, Universidad de Alicante, España Alejandro César Luna Bernal, Universidad de Guadalajara, México